PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRITED READING AND COMPOSITION PADA MATERI ARITMATIKA SOSIAL DI SMP NEGERI 2 - MZN, Moestawa; Halini, Halini; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the application of Cooperative Integrative Reading and Composition (CIRC) learning models in class VII social arithmetic material at SMP Negeri 2 Sungai Raya. The study was reviewed from three aspects, including: the implementation of the syntax of learning, learning activities of students, and learning outcomes of students. The research method used is an experimental method, with a pre-experimental design. The research subjects were grade VII students. Based on data analysis that reviews three aspects, the results are (1) the application of learning syntax is categorized very well with 3.53. (2) the learning activities of students are included in the active criteria that is equal to 73.68% (3) students' learning outcomes classically there are 27 students which is about 79.41% who achieve minimal completeness. The conclusion of this study proves that the Cooperative Integrative Reading and Composition (CIRC) learning model is effectively applied to social arithmetic material class VII in SMP Negeri 2 Sungai Raya.Â Keywords: Cooperative learning model, CIRC type, and social arithmetic